Agreements Exchanged between UMP and Mercedes-Benz (M) Sdn. Bhd. - UMP, PNC (2018)
A Memorandum of Understanding (MoU) was signed between Universiti Malaysia Pahang (UMP) and Mercedes-Benz (Malaysia) Sdn. Bhd. on October 12, 2018 at Banquet Hall, UMP Gambang Campus.